Modernist architecture of Kazakhstan: Preservation strategies - Kustaubayeva, Manar; Nigmetova, Ardak; Kostsova, Aleksandra; Imanbayeva, Zhanerke (project baikal, 2025)
This article examines the renovation practices applied to selected examples of modernist architecture in Almaty – outstanding specimens of Soviet modernism that have significantly contributed to shaping the city’s unique architectural identity. A substantial portion of these structures is currently undergoing reconstruction, which often distorts the original architectural intent and results in the loss of authentic design elements. The primary aim of this research is to develop a comprehensive preservation strategy for Kazakhstan’s modernist architectural heritage, using the city of Almaty as a case study. For this purpose, three sites were analyzed using a comparative study of visual documentation and field observations, resulting in a justification of heritage preservation approaches through digital modeling, which ensures accurate capture of the authentic appearance of buildings.
Keywords: modernism; architectural heritage; renovation; synthesis of the arts; digital modeling